2010
DOI: 10.1148/radiol.10091706
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Hepatic Tumors: Short-term Reproducibility of Apparent Diffusion Coefficients with Breath-hold and Respiratory-triggered Diffusion-weighted MR Imaging

Abstract: Changes in ADCs of less than approximately 30% fall into the range of measurement error. Imaging technique significantly affected ADCs of malignant hepatic tumors. Lesion location and size are potentially influential on the reproducibility of ADC measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 26 publications
8
106
3
Order By: Relevance
“…30,31 Finally, the partial volume averaging effect with the surrounding liver, especially in the case of the very small ROIs in our study, may also have impaired the reliability of the ADC measurements. 32 In this regard, an international consensus preconized a minimum 2-cm ROI diameter in order to avoid inaccuracies in ADC measurements. 33 This might explain the results from Nishie et al 16 who found a significant difference between low-and high-grade HCCs with large-sized lesions [3.6 6 3.1 cm (range, 1-17 cm)].…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Finally, the partial volume averaging effect with the surrounding liver, especially in the case of the very small ROIs in our study, may also have impaired the reliability of the ADC measurements. 32 In this regard, an international consensus preconized a minimum 2-cm ROI diameter in order to avoid inaccuracies in ADC measurements. 33 This might explain the results from Nishie et al 16 who found a significant difference between low-and high-grade HCCs with large-sized lesions [3.6 6 3.1 cm (range, 1-17 cm)].…”
Section: Discussionmentioning
confidence: 99%
“…20 Continuous variables were presented as mean Ϯ SD. Quantitative changes in each parameter were compared by using an unpaired t test between subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Reproducibility measurements of DW-MRI data are necessary to understand the magnitude of variation that can be detected confidently. Both the size and the position of lesions are known to influence reproducibility, with larger lesions being more reproducible [129] . At the time of authoring Kim et al [29] , [119] , Table 9 Estimates of apparent diffusion coefficient values of cancer vs normal tissue/benign disease reported in selected studies on different anatomical regions using a mono-exponential fit Some studies were carried out with more b-values than specified in the following table to compute intravoxel incoherent motion-specific parameters.…”
Section: Reproducibility Of Adc Valuesmentioning
confidence: 99%